The genus Boreviulisoma Brolemann, 1928—an Iberian-N African outlier of a mainly tropical tribe of millipedes (Diplopoda: Polydesmida: Paradoxosomatidae) - Reboleira, Ana Sofia P.s.; Enghoff, Henrik (Zootaxa, 2013)
The genus Boreviulisoma Brolemann, 1928, is revised. The synonymy of Liliputia Attems, 1952, under Boreviulisoma is confirmed, but L. badia Attems, 1951, from Spain, is resurrected, as Boreviulisoma badium, from synonymy under B. li-ouvillei Brolemann, 1928 (the type species of Boreviulisoma) from Morocco. Boreviulisoma barrocalense n. sp. is de-scribed from the subterranean environment of the Algarve, the southernmost province of Portugal. The distribution of the three known species of Boreviulisoma is mapped, main characters of the genus and its species are reviewed and a key to species of the genus is included. The isolated occurrence of Boreviulisoma badium and B. barrocalense n. sp. in the south-ern Iberian Peninsula, together with B. liouvillei and Eviulisoma abadi Mauriès, 1985, in Morocco, as northern outposts of the chiefly Afrotropical-Neotropical tribe Eviulisomatini, is discussed.